Glinide, but Not Sulfonylurea, Can Evoke Insulin Exocytosis by Repetitive Stimulation: Imaging Analysis of Insulin Exocytosis by Secretagogue-Induced Repetitive Stimulations. (6th December 2009) - Aoyagi, Kyota; Ohara-Imaizumi, Mica; Nishiwaki, Chiyono; Nakamichi, Yoko; Nagamatsu, Shinya
Abstract : To investigate the different effects between sulfonylurea (SU) and glinide drugs in insulin secretion, pancreaticβ -cells were repeatedly stimulated with SU (glimepiride) or glinide (mitiglinide). Total internal reflection fluorescent (TIRF) microscopy revealed that secondary stimulation with glimepiride, but not glucose and mitiglinide, failed to evoke fusions of insulin granules although primary stimulation with glucose, glimepiride, and mitiglinide induced equivalent numbers of exocytotic responses. Glimepiride, but not glucose and mitiglinide, induced abnormally sustained[ Ca 2 + ] i elevations and reductions of docked insulin granules on the plasma membrane. Our data suggest that the effect of glinide on insulin secretory mechanisms is similar to that of glucose.